Poly(Ethylene Glycol)–Polylactide Micelles for Cancer Therapy - Wang, Jixue; Li, Shengxian; Han, Yuping; Guan, Jingjing; Chung, Shirley; Wang, Chunxi; Li, Di (Frontiers in Pharmacology, 2018)
For the treatment of malignancy, many therapeutic agents, including small molecules, photosensitizers, immunomodulators, proteins and genes, and so forth, have been loaded into nanocarriers for controllable cancer therapy. Among these nanocarriers, polymeric micelles have been considered as one of the most promising nanocarriers, some of which have already been applied in different stages of clinical trials. The successful advantages of polymeric micelles from bench to bedside are due to their special core/shell structures, which can carry specific drugs in certain disease conditions. Particularly, poly(ethylene glycol)−polylactide (PEG−PLA) micelles have been considered as one of the most promising platforms for drug delivery. The PEG shell effectively prevents the adsorption of proteins and phagocytes, thereby evidently extending the blood circulation period. Meanwhile, the hydrophobic PLA core can effectively encapsulate many therapeutic agents. This review summarizes recent advances in PEG−PLA micelles for the treatment of malignancy. In addition, future perspectives for the development of PEG−PLA micelles as drug delivery systems are also presented.